2007
DOI: 10.1007/s10853-006-0540-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and electrical properties of hot-pressed borosilicate glass matrix composites containing multi-wall carbon nanotubes

Abstract: Borosilicate glass matrix composites reinforced with 10 wt% multiwall carbon nanotubes (CNTs) were fabricated using a conventional powder processing route and uniaxial hot pressing. The microstructure of the composites contained aggregates of CNTs which had not been infiltrated by the viscous glass during hot-pressing leaving a ~9% residual porosity. As a result, the mechanical properties (hardness, elastic modulus, fracture toughness and fracture strength) were not improved in comparison to those of the monol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
58
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 30 publications
3
58
0
Order By: Relevance
“…Powder processing has been applied to various composites systems including borosilicate glass 33,63 , silicon nitride 64-69 alumina, 70,71 , mullite 72 and silica 73 matrix composites containing different concentrations of CNTs (typically 1 -10 vol.%). These investigations have been of mixed success in terms of the quality of the microstructure homogeneity and properties achieved (see section 4).…”
Section: Powder Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Powder processing has been applied to various composites systems including borosilicate glass 33,63 , silicon nitride 64-69 alumina, 70,71 , mullite 72 and silica 73 matrix composites containing different concentrations of CNTs (typically 1 -10 vol.%). These investigations have been of mixed success in terms of the quality of the microstructure homogeneity and properties achieved (see section 4).…”
Section: Powder Processingmentioning
confidence: 99%
“…In principle, the approach provides a means of modifying the wettability and/or adhesion between CNTs and a chosen ceramic matrix, even after high temperature consolidation. Although the idea remains to be explored in detail, coatings of sol-gel silica on CNTs have been shown to improve the mixing quality of the CNTs with borosilicate glass powder 63 , and to provide a degree of thermal oxidation resistance even at 1200 o C in air 38 .…”
Section: Sol-gel Processingmentioning
confidence: 99%
“…However, alumina-CNT composites are previously reported to have lower hardness as compared to monolithic alumina [10,[20][21][22][23][24][25][26] due to various reasons. Jiang et al reported lower hardness and toughness for alumina + 10 vol.% CNT composite due to the degradation of CNTs during sintering [26].…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Though innumerable reports are available on CNT-polymers and CNTceramics composites, very few reports are available on CNT reinforced glass composite. 10,11 Moreover most of the research on CNT-glass composite was undertaken by sol-gel and hot pressed method where porosity and cristobalite formation are the main disadvantages. 10,11 Recently we have reported a method to fabricate SWCNT-borosilicate glass composite by melt-quench technique without any porosity.…”
mentioning
confidence: 99%
“…10,11 Moreover most of the research on CNT-glass composite was undertaken by sol-gel and hot pressed method where porosity and cristobalite formation are the main disadvantages. 10,11 Recently we have reported a method to fabricate SWCNT-borosilicate glass composite by melt-quench technique without any porosity. 12 In this letter, we report the enhanced mechanical properties of the aforesaid composite correlating the cushioning behavior of SWCNTs and plasticity of the composite in higher load.…”
mentioning
confidence: 99%